2014
DOI: 10.1371/journal.pone.0102500
|View full text |Cite
|
Sign up to set email alerts
|

Human Stefin B Role in Cell's Response to Misfolded Proteins and Autophagy

Abstract: Alternative functions, apart from cathepsins inhibition, are being discovered for stefin B. Here, we investigate its role in vesicular trafficking and autophagy. Astrocytes isolated from stefin B knock-out (KO) mice exhibited an increased level of protein aggregates scattered throughout the cytoplasm. Addition of stefin B monomers or small oligomers to the cell medium reverted this phenotype, as imaged by confocal microscopy. To monitor the identity of proteins embedded within aggregates in wild type (wt) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Compared to MG132-, sodium arsenite-, or cadmium chloride-treated cells, a relatively lower number of ProteoStat dyestained structures were detected in control A6 cells. Previous studies have shown a similar phenomenon with prostate cancer, myeloma, astrocyte, and B lymphocyte cells suggesting the presence of ProteoStat-stained aggregated protein in non-stressed cells (Malek et al, 2014;Pacheco et al, 2014;Polajnar et al, 2014;Jagannathan et al, 2015;Koukourakis et al, 2015). It is possible that these control aggregates are associated with vimentin structures given their colocalization with ProteoStat dye-stained protein aggregates.…”
Section: Stress-induced Hsp30 Accumulation In Soluble and Insoluble Psupporting
confidence: 57%
“…Compared to MG132-, sodium arsenite-, or cadmium chloride-treated cells, a relatively lower number of ProteoStat dyestained structures were detected in control A6 cells. Previous studies have shown a similar phenomenon with prostate cancer, myeloma, astrocyte, and B lymphocyte cells suggesting the presence of ProteoStat-stained aggregated protein in non-stressed cells (Malek et al, 2014;Pacheco et al, 2014;Polajnar et al, 2014;Jagannathan et al, 2015;Koukourakis et al, 2015). It is possible that these control aggregates are associated with vimentin structures given their colocalization with ProteoStat dye-stained protein aggregates.…”
Section: Stress-induced Hsp30 Accumulation In Soluble and Insoluble Psupporting
confidence: 57%
“…Would a localized autophagic response be evoked in close proximity to bursting lysosomes in an attempt to rescue cells from the mishap (Meschini et al 2011;Polajnar et al 2014)? Considering that both cysteine cathepsins and legumain are involved in autophagy (Overbye et al 2011), it is conceivable they might themselves even contribute to such pathways helping clean up the cytotoxic mess they themselves have created.…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 99%
“…Stefin B (also termed cystatin B) gene mutations, either dodecamer repeats resulting in lower protein production or missense mutations leading to misfolding, cause a progressive myoclonus epilepsy of type 1 (EPM1) with slow signs of neurodegeneration [28,29]. Similarly to cystatin C, stefin B protects neurons from excessive oxidative stress [30,31] and protein misfolding [32]. Alternative functions, such as amateur chaperone function, have also been suggested from both experimental data and bioinformatic analysis [33].…”
Section: Introductionmentioning
confidence: 99%